The Effect of Population, Education, Minimum Wage and Gross Regional Domestic Product on the Amount of Unemployment in the Regency and City of East Java, 2010-2014 - Hartanto, Trianggono Budi; Masjkuri, Siti Umajah (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2017)
This research aims to analyze the impact of variable population, education (Average Years of School), minimum wage and gross domestic regional product on unemployment in district and cities East Java from 2010 to 2014. The analytical method used panel data regression (pooled data) with the Random Effect Model approach. Results of panel data regression analysis in this research showed population, education (means years school), minimum wage and regional gross domestic product is simultaneously significant positive effect on unemployment in district and cities East Java. Partially, population, education (average year of school) and regional gross domestic product is significant and positive impact on unemployment, while minimum wage has no significant impact on unemployment in district and cities East Java.